2015
DOI: 10.1038/eye.2015.242
|View full text |Cite
|
Sign up to set email alerts
|

Biometric and refractive changes after orbital decompression in Korean patients with thyroid-associated orbitopathy

Abstract: Purpose To determine the biometric and refractive changes after orbital decompression in Korean patients with thyroid-associated orbitopathy (TAO). Methods Retrospective, observational study (between October 2012 and September 2014) was performed. Patients with TAO undergoing orbital decompression for stable proptosis received ophthalmic examinations, including Hertel exophthalmometry, A-scan biometry, autorefraction measures, corneal topography, and wavefront aberration measures, before orbital decompression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Another study reported that patients with GO who underwent orbital decompression showed myopic refractive change through increase in AL and they added possible refractive changes should be considered in cases of GO complaining of decreased visual acuity after orbital decompression. [11] The previous studies have reported that ocular blood flow was increased in patients with GO. Various techniques including Doppler imaging, ocular blood flow tonography, and oculo-dynamometry can ensure more reliable ocular blood flow measurements.…”
Section: Discussionmentioning
confidence: 95%
“…Another study reported that patients with GO who underwent orbital decompression showed myopic refractive change through increase in AL and they added possible refractive changes should be considered in cases of GO complaining of decreased visual acuity after orbital decompression. [11] The previous studies have reported that ocular blood flow was increased in patients with GO. Various techniques including Doppler imaging, ocular blood flow tonography, and oculo-dynamometry can ensure more reliable ocular blood flow measurements.…”
Section: Discussionmentioning
confidence: 95%
“…19 These findings were corroborated by Kim et al who found that axial length (AL) significantly increased after orbital decompression surgery (change in AL = 0.08mm p < 0.001). 20 We hypothesize that the fluctuating volume status of the orbit in TED is a reason for the increased risk of unexpected refractive prediction error in patients with TED. Although TED is thought to classically manifest with an active inflammatory phase, followed by a plateau and an inactive phase, there have been several reports in the literature that might suggest TED flares associated with cataract surgery.…”
Section: Discussionmentioning
confidence: 98%
“… 19 These findings were corroborated by Kim et al who found that axial length (AL) significantly increased after orbital decompression surgery (change in AL = 0.08mm p < 0.001). 20 …”
Section: Discussionmentioning
confidence: 99%
“…The surgical treatment of severe GO known as orbital decompression reduces venous congestion and leads to a decrease in eyelid edema and chemosis, ultimately resulting in significant changes in the corneal curvature and refractive values. 24 …”
Section: Discussionmentioning
confidence: 99%